Perbandingan Kualitas Patient Engagement Pada Empat Pelayanan Spesialis Dasar Di RSUD Haji Provinsi Sulawesi Selatan - K, Andi Tihardimanto (Al-Hikmah, 2014)
Abstract This research aimed to describe and compare the patient engagement quality of the four basic specialist services in the in-patient installation in Haji Local General Hospital of South Sulawesi Province. This research was a comparative descriptive research. The research sample comprised the group respondents of in-patients the four basic specialist services. The result of the research revealed that patient engagement quality as perceived by the patients was categorized as good (73,9%); the patient engagement related to the doctor’s capacity to listen to and encourage the patients to ask questions was categorized as good (78,4%); in making a decisions was not good (63,6%); the ability of the doctor to give and explain the information to patients was good (63,1%). The duration of consultation was good (56,8%); while the empathy given to the patients was categorized as good (83,5%). As for the quality of the patient engagement in the four sub-parts of the basic specialist services, the quality of the patient engagement was significantly different from one another (p=0,000).